From the foundations to the crenellations: essays on temple building in the Ancient Near East and Hebrew Bible - Boda, Mark J.; Novotny, Jamie (Alter Orient und Altes Testament, 2010)
Literaturverz. S. [517] - 561
Literaturverz. S. [517] - 561
Keywords: Temple of Jerusalem (Jerusalem); Bible -- Old Testament -- History of Biblical events; Middle East -- Antiquities; Palestine -- Antiquities; Aufsatzsammlung; Tempel Jerusalem; Bibel / Altes Testament; Geschichte; Tempelbau; Alter Orient